Death penalty and the victims - Simonovic, Ivan; United Nations. Office of the High Commissioner for Human Right ([New York, N.Y.] United Nations, Human Rights Office of the High Commissioner, 2016)
"This publication includes perspectives from a broad range of victims. While some of them are family members of crime victims, others are victims of human rights violations in application of the death penalty, of its brutality and traumatic effects"--Back cove
Preface / Ban Ki-Moon --Introduction. Who are the victims? / Ivan S̆imonović -- Arguments against the death penalty as seen from a victimological perspective / Marc Groenhuijsen, Michael O'Connell -- Does the death penalty serve victims? / Maiko Tagusari -- Listening to victims / Mickell Branham -- Death penalty and the right to life / Mireya García Ramírez -- Escaping the closure trap / Jody L. Madeira -- Does capital punishment bring closure to the victims? / David Johnson -- Victims of wrongful conviction in retentionist nations / Carolyn Hoyle -- In the shadow of the death penalty / Brandon Garrett -- Discrimination and the death penalty / Ross Kleinstuber -- Capital punishment, mental illness, and intellectual disability : the failure to protect individuals with mental disorders facing execution / Sandra Babcock -- Inevitability of arbitrariness : another aspect of victimisation in capital punishment laws / Saul Lehrfrend and Roger Hood -- Cases of the death penalty against international law : Amnesty International's concerns / Salil Shetty -- Death penalty : torture or ill-treatment? / Jens Modvig -- Hidden victims : the families of those facing the death penalty / Susan F. Sharp -- Impact of the death penalty on the children with a parent on death row or executed / Francis Ssuubi -- Ending silence, ending shame / Susannah Sheffer -- Impact of the imposition of the death penalty on families of the convicted in the Caribbean / Florence Seemungal, Lizzie Seal and Lynsey Black -- Socio- psychological challenges of 'Death Row families' / Sandra Joy -- Death penalty and its impact on the professionals involved in the execution process / Florence Seemungal, Lizzie Seal and Lynsey Black --Executioners at work : collateral consequences of executions for officers working on Death Row and in the Death House / Robert Johnson -- Painful then, painful now / Ron McAndrew -- Fighting for clients' lives : the impact of death penalty work on post-conviction capital defence attorneys / Susannah Sheffer -- Death penalty : killing what we instead could be / James R. Acker -- Death penalty as a public health problem / Walter C. Long -- Afterword / Zeid Ra'ad Al Hussei
"Federal Department of Foreign Affairs FDFA."
"Sales no. E.16.XIV.2"--Page facing the title page.
Keywords: Capital punishmen; Victims of violent crime